Can religion kill? The association between membership of the Apostolic faith and child mortality in Zimbabwe - Wei Ha; Stanley Gwavuya; Peter Salama (AOSIS, 2018)
Existing literature has been equivocal about the effect of religion on utilization of health service and health outcomes. While followers of particularized theology hypothesis believe that doctrinal teachings, beliefs and values of religious groups directly influence health access and outcomes, the advocates of the selectivity hypothesis claim that the observed disparities between religious groups mainly reflect differential access to social and human capital which in turn determines health access and outcome rather than religion per se. Using household data from the Zimbabwe Multiple Indicator Monitoring Survey 2009, we find that household heads' affiliation with apostolic faith put children under five years old at greater risk of death compared to other religious groups. This effect remains strong even after controlling for a wide range of socio-economic and demographics characteristics of the households in multivariate logit regressions.